Four-party evolutionary game of collaborative recycling and management of takeaway packaging waste - JIA Yajuan, JI Yuexin (Ziyuan Kexue)
[Objective] In the context of the rapid rise of instant retail and exponential growth of the takeaway industry in the internet era, effective recycling and management of surging takeaway packaging waste is crucial for environmental protection. This study aims to explore the evolutionary game patterns among multiple stakeholders in the recycling and management process and identify key influencing factors and their effects. This will provide decision-making support for achieving collaborative recycling and management of takeaway packaging waste, characterized by multi-stakeholder participation, shared responsibility, and resource sharing. [Methods] Based on the synergy theory, and considering the bounded rationality of different stakeholders in the recycling activities of takeaway packaging waste, a four-party evolutionary game model involving the government, third-party recycling companies, restaurants, and consumers was established. Numerical simulations were conducted using Matlab 2023a software to analyze the sensitivity of different influencing variables. [Results] (1) When the government adopted a high-intensity regulatory strategy, the efficiency of the recycling and management system for takeaway packaging waste increased, and vice versa. (2) Under stringent government regulation, higher reputation conversion rates and greater incentive and penalty mechanisms could effectively motivate restaurants and third-party recycling companies to cooperate in building green recycling channels. (3) The effect of opportunity costs on consumer recycling strategies was not significant, while government subsidies could make consumers’ participation in recycling a practical, long-term, and stable choice. [Conclusion] Effective strategies to improve the recycling efficiency of takeaway packaging waste include: developing recycling policies and industry packaging standards for takeaway packaging waste, strengthening green supply chain management in the takeaway industry, raising the awareness among stakeholders regarding their participation in recycling, and stepping up publicity efforts that promote low-carbon and environmentally friendly behaviors. The research findings can provide policy insights for systematically promoting the development of the takeaway packaging waste recycling and management system, aiming to achieve green and sustainable development and a win-win situation of environmental and economic benefits.